Accurate diagnosis and treatment of isolated mesenteric artery dissections. (April 2020) - Gang, Chen; Xiujuan, Gao; Yingjiang, Xu; Xun, Cui; Dan, Shang; Jianyong, Liu; Bi, Jin
Objectives: Diagnosis and treatment of isolated mesenteric artery dissections (IMAD) are overlooked. The purpose of this study was to assess the clinical feature, possible diagnostic errors and treatment methods. Methods: From January 2010 to December 2017, 99 consecutive patients who were diagnosed with IMAD on computed tomography angiography were enrolled retrospectively. Thirty-nine misdiagnosed patients, false negative, and 60 accurate diagnosis patients with revealed IMAD were compared. In addition, therapeutic schemes were evaluated. Results: Ninety-nine patients participated in this study; 39 patients (34 men, 5 women; median age, 51.41 years, range 38–64 years) were included in group A who were misdiagnosed initial visit; the remaining 60 patients (52 men, 8 women; median age, 52.07 years, range 38–68 years) with IMAD who were diagnosed accurately initial visit were included in group B. Significant differences were observed between the two groups with respect to dissection length (55.26 ± 3.88 mm vs. 43.37 ± 2.75 mm; p  = 0.01), and branch involvement (14 and 9, respectively; p  = 0.04). Ultimately, 33 patients (group A 14 patients and group B 19 patients) underwent invasive interventional therapy, and 66 patients with conservative treatment with antithrombotic agents (group A 25 patients and group B 41 patients). A total of 86 (86.87%) had follow-up computed tomography angiography with a median duration of 24.51 months (range 2–71 months). Three patients died during follow-up. The remaining patients recovered smoothly. Conclusion: Physicians should raise the awareness of IMAD and use the optimal treatment time frame. Diagnosis of IMAD depends on imaging examinations, especially computed tomography angiography. Additionally, conservative management is the most common initial treatment. For patients in whom conservative treatment fails, endovascular and/or surgery may be necessary.